FORMATION OF ETHNOCULTURAL COMPETENCE OF THE FUTURE TEACHERS BY MEANS OF A FOLK ART (Pedagogy of Higher and Secondary Education, 2007)
This article opens ways of formation of ethnocultural competence of the future teachers during mastering symbol shaped system of products of a folk art.
Keywords: ethnocultural competence; symbol-shaped system